Bored with boredom? Trait boredom predicts internet addiction through the mediating role of attentional bias toward social networks - Cannito, Loreta; Ceccato, Irene; Annunzi, Eugenia; Bortolotti, Alessandro; D’Intino, Eleonora; Palumbo, Rocco; D’Addario, Claudio; Di Domenico, Alberto; Palumbo, Riccardo (Frontiers in Human Neuroscience, 2023)
Internet addiction is an emerging issue, impacting on people' psychosocial functioning and wellbeing. However, the prevalence and the mechanisms underlying internet misuse are largely unknow. Like other behavioral addiction disorders, internet addiction insurgence and maintenance may be favored by negative affect such as boredom. In this study, we examined the role of boredom susceptibility, as a personality trait, on predicting the internet addiction risk. Furthermore, we analyzed the attentional mechanisms that may exacerbate dysfunctional internet behaviors. Specifically, we assessed the mediating role of the attentional bias toward social media cues on the relation between boredom susceptibility and internet addiction. Sixty-nine young adults were administered a dot-probe task assessing internet-related attentional bias (AB) and questionnaires measuring internet addiction (IAT) and boredom susceptibility (BS-BSSS). Correlation and t-test analyses confirmed that the tendency to experience boredom and the selective attention toward social network information were related to internet addiction. Furthermore, the mediation model indicated that AB fully explain the link between BS-BSSS and IAT. The study highlighted the crucial role of selective attentional processing behind internet addiction. Current results are useful for both researchers and clinicians, as they suggest that intervention programs for internet addiction should include strategies to cope with dysfunctional cognitive processes.